Desain Pengembangan Modul Pembelajaran Berbasis Pendekatan Saintifik pada Mata Pelajaran Otomatisasi Tata Kelola Sarana dan Prasarana Kelas XI SMKN Ngraho Bojonegoro - Ridha Wahyuningtyas; Novi Trisnawati (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2021)
The purpose of this study was to develop a Scientific-based module in the subject of Automation of Facilities and Infrastructure Management for Class 11 of SMK Negeri Ngraho Bojonegoro. This study uses a 4-D (Four D) development method with designs such as roll definitions, design, development design, development, and development, and this study uses XI OTKP research at SMK Negeri Ngraho. This research uses research and development (R&D) which means "The research method used to produce certain products. This research starts at the defining stage which consists of five initial analyzes, student analysis, task analysis, concept analysis, and goal specification. Then, the next step is the design which consists of teaching-approved materials, learning modules using science in the subject of automation of class XI facilities and infrastructure management. The results of the design produced by the module were developed using science. In this study there are limitations of the study, namely: 1) Automated Facilities and Infrastructure Management module which researchers will develop only for class XI OTKP of SMK Negeri Ngraho in the even semseter. 2) the module developed by reserchers uses the 4-D development model from Thiagarajan and is limited to the second stage, namely the design stage 3) the results of this study can only be used in class XI of SMK Negeri Ngraho, Bojonegoro.